Higher estimated dietary intake of live microbes is associated with lower mortality in US adults - Liu, Xuna; Wang, Yiwen (Frontiers in Nutrition, 2025)
BackgroundFew studies have discussed the health benefits of total dietary intake of live microbes (TDIIM). We investigated the relationship between daily estimated TDIIM and mortality in US adults.Materials and methodsThis cohort study included subjects ≥18 years from the 1999–2018 NHANES and their mortality data through December 31, 2019. The TDIIM counts were estimated based on a prior classification system, with foods categorized into low (<10^7 CFU/g), medium (10^7–10^10 CFU/g), and high (>10^10 CFU/g) levels of live microbes. Individual intakes were calculated by multiplying the microbial levels by the corresponding grams of food consumed. Weighted Cox regression models, Kaplan–Meier survival curves, and restricted cubic splines (RCS) were used to estimate the association between all-cause and cardiovascular (CVD) mortality and TDIIM.ResultsAmong 52,383 participants, during a median follow-up period of 118.75 months, a total of 7,711 deaths were recorded, of which 1,985 were CVD deaths. In the weighted Cox regression model, compared to participants with low TDIIM, those with high intake have lower risks of all-cause mortality (HR 0.91; 95% CI, 0.82–1.00; P for trend, 0.01), and CVD mortality (HR 0.77; 95% CI, 0.63–0.95; P for trend, 0.005). In the RCS analysis, the relationship between TDIIM and all-cause mortality exhibited a non-linear pattern with a gradual decline followed by a plateau at higher intakes, while a linear decreasing trend was observed with CVD mortality. Kaplan–Meier survival curves showed that participants with low TDIIM had a higher risk of all-cause mortality and CVD mortality.ConclusionIn this cohort study of US adults, a higher estimated TDIIM reduced the risk of all-cause and CVD mortality. These findings suggest that the ingestion of live microbes in the diet may be advantageous for human health.